A Holistic Approach to Alleviating Water Poverty in Gresik Regency - Ari, Ismu Rini Dwi; Dwi Purnamasari, Wulan; Aulia, Nasya; Mayori, Indriya Mardiana (Indonesian Journal of Geography, 2024)
The lack of access to safe drinking water and the insufficient provision of individual drinking water needs are among the defining characteristics of slum areas. This study investigates the extent of this problem in Gresik Regency, East Java, Indonesia, a region characterized by the ubiquity of slum settlements across all sub-districts. The study aims to provide a comprehensive understanding of clean water access, water quality, and community capacity in managing water resources with implications for achieving sustainable housing. This study assesses water poverty levels using the Water Poverty Index (WPI), which considers five dimensions: resource availability, accessibility, capacity, usage efficiency, and environmental sustainability. The result shows the WPI of Gresik Regency revealed a score of 73.95, indicating a low level of water poverty, suggesting that the region's water security is in a good condition. Among the five dimensions constituting the WPI, the environmental dimension falls into the category of relatively high WPI or environmental poverty, with a score of under 50. This indicates that while access to water is available and affordable, issues related to waste management and future water resilience remain low. Water scarcity in the Gresik District is an illustration of global challenges related to water poverty, such as in Myanmar, India and South Africa, which have WPI values below 55. This research emphasizes the importance of a holistic approach in managing water resources by prioritizing environmental quality as the main priority